2020
DOI: 10.1108/apjie-06-2019-0041
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide role of women entrepreneurs in economic development

Abstract: Purpose The contribution of women entrepreneurs is still invisible and needs to be properly investigated. The purpose of this paper is to investigate this relationship by measuring women entrepreneurship and economic development at global level. Design/methodology/approach Secondary data has been retrieved from Female Entrepreneurship Index Report 2015, Human Development Report 2015 and KOF Index of Globalization 2015. Cross-sectional data is used from 69 countries of the world. Multiple regression is applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 37 publications
5
52
0
5
Order By: Relevance
“…Entrepreneurship driven by deep technology offers women in science and technology a novel career possibility (Etzkowitz, 2013a). Women's entrepreneurship is important for social well-being (Sajjad et al, 2020). It leads to women's social and economic empowerment, particularly in developing countries with higher gender differences in occupational statuses and rigid patriarchal systems (Olarevaju and Fernando, 2020).…”
mentioning
confidence: 99%
“…Entrepreneurship driven by deep technology offers women in science and technology a novel career possibility (Etzkowitz, 2013a). Women's entrepreneurship is important for social well-being (Sajjad et al, 2020). It leads to women's social and economic empowerment, particularly in developing countries with higher gender differences in occupational statuses and rigid patriarchal systems (Olarevaju and Fernando, 2020).…”
mentioning
confidence: 99%
“…Women’s entrepreneurship contributes widely through insights and the investment of a lot of energy and capital assets to their networks, plus they produce jobs and create extra work for providers and other side project business linkages ( Polas et al, 2021 ). Women-owned organizations have expanded in recent years ( Sajjad et al, 2020 ), and a developing measure of exploration shows that developing countries have neglected to address gender obstructions to critical economic development ( Athanne, 2011 ). Nonetheless, the study discovered that men have a higher inclination for business behavior than females ( Salahuddin et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Women entrepreneurs are the fastest growing entrepreneurs in the world (Brush et al, 2006;Brush & Cooper, 2012). They bring many assets and skills to the global market (Jalbert, 2000;Sajjad et al, 2020). In contrasting with developed nations, poverty, widowing, divorces and lesser family income may have caused women to enter to the business world in developing nations (Carter et al, 2001;Brush et al, 2004;Sajjad et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They bring many assets and skills to the global market (Jalbert, 2000;Sajjad et al, 2020). In contrasting with developed nations, poverty, widowing, divorces and lesser family income may have caused women to enter to the business world in developing nations (Carter et al, 2001;Brush et al, 2004;Sajjad et al, 2020). However, Suriyamurthi et al (2018) revealed different obstacles faced by women in developing nations a they try to develop their businesses.…”
Section: Literature Reviewmentioning
confidence: 99%